Do ESP teachers need to be subject specialists? A critical examination - Reswari, Girindra Putri Ardana; Patria, Aditya Nur; Alfarisy, Fitri (Universitas Negeri Semarang, 2025)
This study examines the necessity of subject-matter expertise for effective English for Specific Purposes (ESP) instruction within higher education. Using a qualitative document analysis approach, twenty theoretical and empirical studies published between 1977 and 2025 were synthesised through thematic analysis. Three dominant themes emerged: (1) collaboration and interdisciplinary insight, (2) teacher attitudes toward subject knowledge, and (3) teacher training and professional development. The findings indicate that effective ESP instruction in universities does not depend primarily on teachers becoming subject specialists. Rather, authenticity and disciplinary relevance are most successfully achieved through structured collaboration with field experts, instead of individual mastery of specialised content. Teacher disposition, particularly openness, adaptability, and respect for learners’ disciplinary expertise was found to strongly mediate instructional success in tertiary classrooms. In addition, corpus-based pedagogy, discourse and genre awareness, digital literacy, and intercultural communication emerged as core areas of professional preparation for ESP teachers. The study concludes that ESP teacher competence in higher education is best characterised by collaborative engagement, pedagogical flexibility, and reflective professionalism rather than disciplinary expertise alone underscoring the need for universities to establish sustainable collaboration frameworks and continuous professional development systems to support the academic and professional demands of ESP in higher education.